Treatment of severe bimaxillary protrusion with miniscrew anchorage: treatment and complications - Mimura Hiroshi (Sciendo, 2023)
Problems involving excessive face height and severe bimaxillary protrusion are usually treated with orthognathic surgery. When this form of treatment is rejected, retraction and intrusion of the anterior teeth using skeletal anchorage afforded by miniscrews may be employed.